Ernst Lothar Schriftsteller, Kritiker, Theaterschaffender - Heißler, Dagmar (2016)
The monograph explores the life, work and legacy of the Austrian writer, director and producer Ernst Lothar (1890-1974) through the analysis of hitherto unpublished correspondence as well as other unpublished writings/documents from his estate, giving ample consideration to the reception of Lothar's oeuvre.